RNA interference targeting apolipoprotein C-III with ARO-APOC3 in healthy volunteers mimics lipid and lipoprotein findings seen in subjects with inherited apolipoprotein C-III deficiency. (25th November 2020) - Schwabe, C; Scott, R; Sullivan, D; Baker, J; Clifton, P; Hamilton, J; Given, B; San Martin, J; Melquist, S; Watts, G.F; Goldberg, I; Knowles, J.W; et al.
Abstract: Background: Individuals with triglycerides (TGs) ≥1, 000 mg/dL (11.1 mmol/L) are at increased risk of acute pancreatitis. Genetic studies indicate that individuals with apolipoprotein C-3 (APOC3) loss-of-function mutations have low TGs, reduced cardiovascular risk and no observed adverse phenotype. RNA interference (RNAi) with ARO-APOC3 has shown deep and durable knockdown (KD) of APOC3 after single doses in healthy volunteers (HVs, presented at AHA 2019) with good tolerability. We report here initial results using multiple doses of ARO-APOC3 to silence APOC3 expression in HVs. Methods: ARO-APOC3 was administered subcutaneously to HVs on days 1 and 29 at doses of 10, 25 or 50 mg (n=4 per group). Measured parameters included plasma concentrations of APOC3, LDL-C, TGs, VLDL-C and HDL-C. Results: All HVs have received both doses and follow-up for most parameters is available through week (wk) 14 (10 wks after second dose) for the 10 and 25 mg doses and through wk 10 for 50 mg. Mean nadir for APOC3 levels occurred at wk 3 for 10 mg (−73%) and remained similar at wk 10 (−66%), at wk 6 for 25 mg (−90%) with no change at wk 10 and at wk 2 for 50 mg (−94%) unchanged at wk 8. TGs fell faster in the 50 mg group (wk 1: 10 mg −41%; 25 mg −47%; 50 mg −72%). By wk 6 the 25 and 50 mg results were similar (−68% and −74%, respectively) and remained similar through wk 14. 10 mg was less active with a nadir of −56% and mean reductions between 42% and 56% post-nadir. VLDL-C values mirrored TGs. LDL-C reductions were more modest and did not manifest a dose response. Mean nadirs (−23–26%) occurred 4–6 wks after the first dose, again with minimal change through 10–14 wks of follow-up. Consistent with genetic studies, HDL-C increased to a maximum at approximately wk 8 (10 mg +42%, 25 mg +48%, 50 mg +84%). ARO-APOC3 was well tolerated without serious or severe adverse events or dropouts related to drug. The most common adverse events were mild injection site AEs and headache. Conclusions: Genetic deficiency of APOC3 is associated with substantial reductions in TGs, VLDL-C and increases in HDL-C without an adverse phenotype. Using RNAi to selectively suppress APOC3 production mimics these lipid and lipoprotein effects, with a duration of at least 10 weeks following a second dose and with good tolerability over 16 wks using doses ranging from 10 to 50 mg. Investigation of optimal dosing regimen is ongoing, especially with respect to dosing interval. This therapeutic approach has potential for treating patients with chylomicronemia at risk of pancreatitis. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Arrowhead Pharmaceuticals